Human Resource Management Practices and Performance of Tertiary Institutions in Ondo State, Nigeria - Emmanuel, A. O.; Paul, O. I. (BOHR International Journal of Advances in Management Research, 2023)
Human resources (HR) must be acknowledged and recognized as an organization’s most valuable asset and the driving force in creating and sustaining competitive advantage in the global marketplace. Challenges of ineffective planning, management, and application of HR functions have been the major issues affecting the rate of employee turnover in organizations. The purpose of this study is to investigate the effects of HR management practices on tertiary institution performance in Ondo State, Nigeria. A sample size of 327 was taken from a population of 1776 using Taro Yamane’s (1964) formula, and a stratified sampling technique was adopted. The questionnaire was recovered in 324 copies, accounting for 99.08% of the total for analysis. The data were analyzed through ordinary least square (OLS) regression, and it was found that the calculated t-statistics score of 1.645 is less than the t-statistics score of the four hypotheses. The null hypotheses were rejected, while alternative hypotheses of 2.127 and 2.483 were accepted. According to the findings of the study, HR management practices have a significant impact on the performance of higher education institutions in Ondo State, Nigeria. It is suggested that effective planning, well-managed implementation, and a policy free of tribalism and nepotism—a policy free of bias—will create a competitive advantage and positively impact the performance of tertiary institutions, particularly Rufus Giwa Polytechnic, Owo.